Continuidade de cuidados à pessoa com enfarte agudo do miocárdio - Cláudia Isabel Neves Pacheco da Silva; Florinda Laura Ferreira Rodrigues Galinha de Sá; Maria Teresa Leal (Nursing Research, Innovation and Development Centre of Lisbon (CIDNUR) of the Nursing School of Lisbon (ESEL), 2019)
Consultar PDF